Obesity prevention: the role of policies, laws and regulations - Swinburn, Boyd A (BioMed Central, 2008)
The commercial drivers of the obesity epidemic are so influential that obesity can be considered a robust sign of commercial success – consumers are buying more food, more cars and more energy-saving machines. It is unlikely that these powerful economic forces will change sufficiently in response to consumer desires to eat less and move more or corporate desires to be more socially responsible. When the free market creates substantial population detriments and health inequalities, government policies are needed to change the ground rules in favour of population benefits. Concerted action is needed from governments in four broad areas: provide leadership to set the agenda and show the way; advocate for a multi-sector response and establish the mechanisms for all sectors to engage and enhance action; develop and implement policies (including laws and regulations) to create healthier food and activity environments, and; secure increased and continued funding to reduce obesogenic environments and promote healthy eating and physical activity. Policies, laws and regulations are often needed to drive the environmental and social changes that, eventually, will have a sustainable impact on reducing obesity. An 'obesity impact assessment' on legislation such as public liability, urban planning, transport, food safety, agriculture, and trade may identify 'rules' which contribute to obesogenic environments. In other areas, such as marketing to children, school food, and taxes/levies, there may be opportunities for regulations to actively support obesity prevention. Legislation in other areas such as to reduce climate change may also contribute to obesity prevention ('stealth interventions'). A political willingness to use policy instruments to drive change will probably be an early hallmark of successful obesity prevention.